The Effect of an Educational Video on Physical Activity for Diabetes Prevention among Obese High School Students in Yogyakarta - Jannah, Miftahul; Aji, Arif Sabta; Sari, Pramitha; Afifah, Effatul (Journal of Global Nutrition, 2024)
The association of obesity with type 2 diabetes mellitus (T2DM) in adolescents has increased globally over the past 2 decades. Thus, it must be prevented and overcome with particular management. The study aimed to analyze the impact of video education on physical activity for the prevention of T2DM among obese high school students in Mergangsan district, Yogyakarta. This was a quasi-experimental study with one group pre and post-test design. Educational videos about the introduction to physical activity education were made and given to students. A total of 47 obese adolescents were recruited and tested for physical activity using the Physical Activity Questionnaire for Adolescents questionnaire. (PAQ-A). The data was processed and analyzed using the Wilcoxon test with SPSS version 23.0. The results of the study were obtained before video education, physical activity in students with obesity was classified as mild (66%). After the video education was given, the physical activity of the majority was moderate (78.7%). There was an association between video education media and physical activity for the prevention of diabetes mellitus in students (p<0.001). The school is expected to continue to provide health advice to students, especially on obesity students to prevent T2DM in adolescents, and the use of educational media with video will be more effective.